Effect Of Changes In The Korean Accounting Environment On The Productivity Of Accounting Firms - Kang, Sun Min; Hwang, In Tae; Hur, Kang Sung (Journal of Applied Business Research, 2017)
To investigate how changes in the accounting environment in Korea affect firm productivity, this study analyzes productivity by firm size and labor type from 2000 to 2014, using a Cobb–Douglas production function. We find that (1) the greater the management advisory (tax) revenue, the greater the total revenue in large (small) accounting firms; and (2) marginal revenue is greatest for partners, followed by certified public accountants and general employees. In particular, partners’ contribution to large accounting firms improved after 2007, whereas general employees made a significant positive contribution to total revenue before 2007.
Keywords: Accounting Environment; Accounting Firms; Production Function; Marginal Revenue